Tax on Land and Building Acquisition (BPHTB) Imposition Following Binding Sale and Purchase Agreements Under Law No. 1 of 2022 - Benita Dita Rezanti; Moh Saleh (Transpublika Publisher, 2026)
Local taxes are a crucial instrument for achieving regional independence by optimizing local revenue, notably through the Tax on Acquisition of Land and Building Rights (BPHTB). BPHTB is imposed on every acquisition of such rights and must be regulated by law as mandated by Article 23A of the 1945 Constitution. Recent tax reform through fiscal decentralization has altered the regulation of when BPHTB is payable. Specifically, Article 49 letter a of Law Number 1 of 2022 stipulates that BPHTB is payable on the date of signing the Sale and Purchase Agreement (PPJB). This provision is reinforced by Government Regulation Number 35 of 2023 and was recently constitutionally tested; the Constitutional Court Decision Number 117/PUU-XXI/2023 rejected the judicial review request concerning this norm. This study analyzes the legal implications of designating the PPJB as the basis for determining BPHTB liability and the legal protection available for buyers. The research method used is normative legal with a legislative and conceptual approach. The findings indicate that determining the PPJB as the basis for imposing BPHTB potentially creates legal uncertainty and disadvantages for buyers. This is because, legally, the acquisition of rights to land and/or buildings only occurs after the signing of the Deed of Sale and Purchase (AJB) before a Land Deed Official (PPAT) and its subsequent registration, in accordance with prevailing laws and regulations. Consequently, harmonization of norms is necessary to ensure legal certainty and fairness for taxpayers.